The Effect of Problem Based Learning Applied With Blended Learning on Students’ Problem Solving Skills - Abdul Haris Odja; Maryam Hasan; Mursalin Mursalin (STKIP Singkawang, 2022)
This research aims to determine the influence of the PBL model applied through blended learning on improving the problem-solving ability of learners on the concept of light topic physics at the junior high school / MTs level. The research method used by the one group pretest posttest design data was obtained through the provision of a problem-solving test consisting of pre-test and post-test. After the pre test, blended learning was conducted 3 times after that post test was carried out. The sample in the study was a class VIII student at integrated MTs in one of Gorontalo's 25 cities. Research and analysis results show the influence of blended learning on problem-solving skills. The ability to solve problems can be seen from the improvement of learners' problem-solving ability on the concept of light. This can be seen from the comparison of the value obtained in the pre-test and post-test analyzed using N-Gain which is as wide as 0.77 with a high interpretation. Other influence indicators can be seen from the pretest average of 37% while the posttest average is 86%. Improvements also occur in all problem solving indicators.